PHYSICAL AND CHEMICAL CHARACTERISTICS INTERPRETATION FOR GROUNDWATER QUALITY ASSESSMENT IN THE COASTAL AREA, NORTH KELANTAN, MALAYSIA (Interpretasi Karakterisasi Fisika dan Kimia Untuk Penilaian Kualitas Airtanah di Area Pesisir, Kelantan Utara, Malaysia) - Nur Islami; Muhammad Nor; Muhammad Rahmad (Jurnal Manusia dan Lingkungan, 2015)
ABSTRACTPhysical and chemical groundwater interpretation has been done in order to characterize and assess its associated problem in the coastal area, North Kelantan, Malaysia. A total of thirty three groundwater samples that consisted of sixteen groundwater samples were collected directly from existing well and together with seventeen groundwater data obtained from government agency, were used in this study. The depth of groundwater sample was varied from the shallow (3.5 m) to the deeper (130 m) aquifer. The physical groundwater characteristics were measured directly at the site just after the groundwater collected. The chemical content of the groundwater sample were analysed using Ion Chromatography (IC) and Inductively Coupled Plasma (ICP). Finally the data was presented and interpreted using the bivariate and piper diagram to improve interpretation and analysis of the whole data. Analysis result of the groundwater sample indicates that the shallow aquifer can be categorized as fresh water. In the zone with marine soil deposit, chloride and sulphate concentration tend to be higher in the water sample. However, the concentration of water sample is still within the accepted limit for human consumption. In places with relatively higher usage of chemical fertilizer, the groundwater sample exhibits higher nitrate concentration more than limit of safe for human consumption (>45 mg/L). K, Ca, Mg and Na content have a positive correlation with chloride concentration in deeper aquifer, indicating that the ions are derived from the same source of saline waters. The relationship between Cl/HCO3 ratios and chloride also shows that the fresh groundwater and seawater mixing in aquifer, and the samples with lower ratios can be categorized as fresh waters. In the shallow aquifer most ions exhibit a poor correlation to chloride indicating that such ions are derived from a different source.ABSTRAKInterpretasi karakter fisika dan kimia air tanah telah dilakukan untuk menilai kualitas air tanah dan masalah masalah yang berhubungan dengannya di zona pesisir, Kelantar Utara, Malaysia. Sebanyak tiga puluh tiga sampel airtanah yang terdiri dari enam belas sampee airtanah yang di ambil langsung dari sumur dan bersama dengan tujuh belas data sampel airtanah diperoleh dari agensi pemerintah digunakan pada penelitian ini. Kedalaman air tanah bervariasi dari yang akuifer dangkal (3,5 m) sampai ke yang dalam (130 m). Karakter fisika air tanah di ukur secara langsung di lokasi saat setelah air tanah di ambil. Kandungan kimia sampel air tanah dianalisa dengan menggunakan Ion Chromatography (IC) and Inductively Coupled Plasma (ICP). Data-data yang diperoleh di presentasikan dan diinterpretasi menggunakan diagram bivariate dan diagram piper untuk meningkatkan interpretasi dan analisa data secara keseluruhan. Hasil analisa sampel airtanah mengindikasikan bahwa akuifer yang dangkal dapat dikategorikan sebagai air segar. Pada zona pengendapan laut, kadar klorid dan sulfat dalam air tanah cenderung tinggi dalam sampel air. Namun kandungan ini masih dalam kategori aman untuk dikonsumsi oleh manusia. Pada lokasi yang banyak penggunaan pupuk kimia, sampel airtanah memperlihatkan kandungan nitrat relative tinggi, yang melebihi batas aman untuk dikonsumsi oleh manusia (>45 mg/L). Kadar K, Ca, Mg dan Na memiliki hubungan yang positif dengan kandungan klorid pada aquifer yang dalam, ini mengindikasikan bahwa ion-ion dalam air adalah berasal dari sumber air asin yang sama. Hubungan antara rasio Cl/HCO3 dan chloride juga menunjukkan bahwa airtanah yang segar and air laut bercampur di dalam aquifer, dan sampel air dengan rasio yang rendah bisa dikategorikan air segar. Untuk aquifer yang dangkal, kebanyakan ion menunjukkan korelasi yang tidak linier dengan klorid yang mengindikasikan bahwa ion-ion tersebut berasal dari sumber yang berbeda.